Does abscisic acid affect strigolactone biosynthesis - López-Ráez, Juan A; Kohlen, Wouter; Charnikhova, Tatsiana; Mulder, Patrick; Undas, Anna K; Sergeant, Martin J; Verstappen, Francel; Bugg, Timothy D.H; Thompson, Andrew J; Ruyter-Spira, Carolien; Bouwmeester, Harro (The New phytologist, 2010)
Strigolactones are considered a novel class of plant hormones that, in addition to their endogenous signalling function, are exuded into the rhizosphere acting as a signal to stimulate hyphal branching of arbuscular mycorrhizal (AM) fungi and germination of root parasitic plant seeds. Considering the importance of the strigolactones and their biosynthetic origin (from carotenoids), we investigated the relationship with the plant hormone abscisic acid (ABA). Strigolactone production and ABA content in the presence of specific inhibitors of oxidative carotenoid cleavage enzymes and in several tomato ABA-deficient mutants were analysed by LC-MS/MS. In addition, the expression of two genes involved in strigolactone biosynthesis was studied. The carotenoid cleavage dioxygenase (CCD) inhibitor D2 reduced strigolactone but not ABA content of roots. However, in abamineSG-treated plants, an inhibitor of 9-cis-epoxycarotenoid dioxygenase (NCED), and the ABA mutants notabilis, sitiens and flacca, ABA and strigolactones were greatly reduced. The reduction in strigolactone production correlated with the downregulation of LeCCD7 and LeCCD8 genes in all three mutants. The results show a correlation between ABA levels and strigolactone production, and suggest a role for ABA in the regulation of strigolactone biosynthesis.